A Comparative Study on Vidangadi Churna and Amrutadya Guggul in the Management of Sthoulya with special reference to Obesity - Joshi, Yougandhar Santosh (International Research Journal of Ayurveda & Yoga, 2022)
Background: Sthoulya is a disorder dominated by medadhatu due to abnormal accumulation of meda in Gatra pradesha specifically in Sphik, Udara, Stana and Gala. It is caused by morbid kapha dosha initially and later pitta and Vaata involved in its pathogenesis. This vitiated Dosha or Doshas afflict. The medadhatu involving medovaha srotas produces the related symptom of its own srotas. Further in later stage due abnormal accumulation of Abadha apachita meda in other respective srotas exhibits lakshanas like Javoparodha, Ayusohrasa, and Swedabadha etc. as its complication. The mode of onset is usually gradual depending upon the Nidana‟s like Atisampurna aahara, Avyaayama, Manasika bhava‟s, Beejadoshaja and by Nidanarthakara karana‟s. The involvement of pitta and vaata dosha‟s along kapha dosha in the pathogenesis of Sthoulya can be well appreciated by their symptoms like Swedadhikya, Atikshudha, Ati Pipasa, Dourgandhya, Javoparodha, Dourbalya, and Utshahani etc Aim: To assess the clinical efficacy of Vidangadi churna and Amrutadya guggul in the management of Sthoulya (obesity). Materials and Methods: The clinical studies were conducted by the Randomized Comparative Clinical Study method; this method compared the clinical efficacy of Vidangadi churna and Amrutadya guggul in the management of Sthoulya (obesity). Result: In Group A, 2 patients (10%) were shown marked improvement, 16 patients (80%) were shown moderate improvement and 2 patients (10%) were shown mild improvement. In Group B, 3 patients (15%) were shown marked improvement, 15 patients ( 75% ) were shown moderate improvement and 2 patients (10% ) were shown mild improvement. Conclusion- There is no much difference in the results of the both the treatment. Both the drug significantly effective.